ICUC - International Centre for Underutilized Crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The ICUC is an autonomous, non-profit making, scientific research and training centre. It was established in 1988 to address ways of increasing the use of underutilized crops both for food, medicinal and industrial products, and also for...